Insulin Pump Therapy in Nursing Practice: Patient Education, Glycemic Monitoring, and Clinical Safety - Al-Qahtani, Sultan Falah Sultan; Zahrah Hussein Shabani,; Mada Mohammad Al-Otaibj,; Zahra Mesfer Summan Al Fayi,; Shaykhah Rasheed Binmozan,; Manal Ghazi Alharthi,; Khulud Abdullah Aldosseri,; Areej Mahboub Al Samti,; Badr Talal Boydr Alanizi, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Diabetes mellitus affects over 500 million people globally, with type 1 diabetes requiring lifelong insulin therapy. Insulin pump therapy, or continuous subcutaneous insulin infusion (CSII), has evolved as a cornerstone for intensive insulin management, offering improved glycemic control and flexibility compared to multiple daily injections. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To explore the clinical significance, operational principles, and nursing interventions associated with insulin pump therapy, emphasizing patient education and safety. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive review of historical developments, device components, insulin delivery mechanisms, and evidence-based nursing practices was conducted, integrating clinical trials and guidelines to outline best practices for inpatient and outpatient care. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> CSII improves glycemic control, reduces hypoglycemia risk, and enhances patient satisfaction. Advanced features such as bolus calculators, auto-mode algorithms, and predictive low-glucose suspend systems further optimize outcomes. However, therapy introduces risks including infusion-site complications, rapid-onset hyperglycemia, and diabetic ketoacidosis during delivery interruptions. Nursing interventions—such as structured education, infusion-site monitoring, and contingency planning—are critical for safety. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Insulin pump therapy represents a clinically significant advancement in diabetes care, requiring interprofessional collaboration and vigilant nursing oversight to maximize benefits and minimize risks.